The use of fly ash as a part of the formingironphosphate cold-hardening mixes - Usenko , R.V.; Barkar , R.R.; Shemet , V.Yu.; Taranov , A.A.; Bilyi , A.P.; Yakymenko , D.Yu. (Theory and Practice of Metallurgy, 2025)
Use of fly ash in the composition of molding and core mixtures as a partial substitute for quartz sand. Methodology. Methods for determining the main technological parameters of molds and cores correspond to those used in specialized production. Findings. Compositions of multicomponent iron phosphate molding CTS based on dispersed technogenic materials have been developed as a replacement for traditionally used materials. Originality. The possibilities of using fly ash in fresh and regenerated cold-hardening iron phosphate mixtures as a filler and/or a stabilizer of the granulometric composition have been identified. Practicalvalue. The use of technogenic materials as a replacement for traditionally used ones will reduce the costs of casting production and improve the environmental situation in the region where the foundry is located.